Impact on Revenue from E-Banking in International Banks in India During COVID-19 - Sankhala, Bhavya (Digital Repository of Theses, 2025)
This study assesses the influence of e-banking on revenue generation by international banks in India during the COVID-19 pandemic. The outbreak of the COVID-19 pandemic led to a rush for financial institutions to shift quickly from traditional brick-and-mortar banking models to digital channels because physical branches experienced restrictions and lockdowns. With the advancement of technology, electronic banking platforms and other electronic financial services have become the mode of banking for customers. This shift caused unprecedented growth in digital transactions, which raises questions about how these changes affect the financial performance and revenue streams of international banks in India. Based on extensive analysis of transactions, customer behavior patterns, and financial reports by some of India's international banks, this thesis explores the various ways ebanking influenced three key revenue drivers: transactional fees, new product offerings that are digital, and customer acquisition/retention. In that regard, significant increases in digital banking services' adoption were discovered, with various customers choosing to use mobile and online transactions on account of ease, safety, and social distancing measures. Consequently, this hike in digital engagement translated into high transaction volumes for the banks involved and boosted fee-based revenues while further reducing operational costs in terms of fewer physical infrastructural requirements. However, the study also highlights several challenges international banks in India face during this period that includes the cybersecurity threats because of the increase in digital transactions, the issues of the digital divide that might affect the unbanked and underbanked population, and the need for continuous investment in digital infrastructure. Despite these inhibitive factors, the study concluded that revenues from e-banking services contributed positively to the financial performance of international banks. This underscores the role of digital transformation in future development and sustainability in the banking sector. The study acknowledges that to take advantage of the long-term revenue potential that ebanking offers, as well as to reduce the risks connected with digital adoption, global banks must keep coming up with new ideas and improving their digital banking strategies. Furthermore, it recommends that banks engage in digital literacy training, cybersecurity measures, and infrastructure improvements to promote inclusive growth and profitability in a post-pandemic economy.